PENGARUH PEMBERDAYAAN PSIKOLOGIS TERHADAP KINERJA KARYAWAN DENGAN PERILAKU KEWARGAAN ORGANISASI SEBAGAI VARIABEL MEDIASI PADA KARYAWAN PT. TELKOM WITEL ACEH - Adriansyah Adriansyah, Ade Irma Suryani (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2018)
Abstract: This study aims to determine the effect of Psychological Empowerment on Employee Performance with Organizational Citizenship Behavior as mediation variable. The sample used in this study are employees of PT. Telkom Witel Aceh. This research method used questionnaire as research instrument. Probability Sampling is used as a sampling technique with Census method. Hierarchical Linear Modeling (HLM) analysis method is used as a method of analysis to determine the effect of the variables involved, Taking 70 employees of PT. Telkom Witel Aceh as correspondent. The results showed: 1) Psychological Empowerment have positive and significant impact on Employee Performance. 2) Psychological Empowerment have positive and insignificant effect on Organizational Citizenship Behavior. 3) Organizational Citizenship behavior have positive and significant impact on Employee Performance. 4) Organizational Citizenship Behavior as Mediation have positive and insignificant effect on Psychological Empowerment and Employee Performance variable at PT. Telkom Witel Aceh.Keywords :    Psychological Empowerment, Employee Performance, Organizational Citizenship Behavior.